Economic Analysis of Charitable Donations - Moon Young Kang; Byungho Park; Sanghak Lee; Jaehwan Kim; Greg Allenby (Journal of Marketing and Consumer Behaviour in Emerging Markets)
This paper examines the effect of message characteristics on donation behavior using an economic model of giving. The utility of giving can come from one’s own contribution and possibly from the combined contributions of others. Donors are assumed to be constrained utility maximizers, and the message attributes affect the degree to which they react altruistically or egoistically. The model is estimated with data from an incentive-aligned study of South Korean consumers, and implications for message optimization and donor targeting are explored.